Mindsets and Self-Concepts About Self-Regulated Learning: Their Relationships With Emotions, Strategy Knowledge, and Academic Achievement - Karlen, Yves; Hirt, Carmen Nadja; Liska, Alina; Stebner, Ferdinand (Frontiers in Psychology, 2021)
Being a self-regulated learner and believing that deliberate strategy use might be an effective way of overcoming learning challenges is important for achieving academic success. Learners' self-theories about their abilities might explain why some students are more inclined to engage in self-regulated learning (SRL) than others. This study aims to investigate the relationships between students' mindsets and self-concepts about SRL and their correlation with enjoyment, boredom, strategy knowledge, and academic achievements. As covariates, we included gender, age, and academic track. We surveyed 244 students (46.3% female) from the lower secondary school level with a mean age of 14.57 years. The results revealed that mindsets about SRL support more adaptive learning emotions (i.e., higher enjoyment and lower boredom) and positively relate to students' strategy knowledge. The students' self-concepts about SRL are positively related to their enjoyment and academic achievements. Gender-specific differences between the students revealed a disadvantage for the boys, who had lower self-concepts about SRL, lower strategy knowledge, and lower academic achievements in comparison to the girls. Furthermore, the study also revealed that students in the lower academic track adhered more to a fixed mindset about SRL and had lower strategy knowledge than their peers in the higher academic track. Finally, we found an indirect relationship between mindset about SRL and academic achievement via self-concepts about SRL. Overall, our results emphasize the importance of students' mindsets and self-concepts about SRL for their learning and academic achievements.